MiR-107 confers chemoresistance to colorectal cancer by targeting calcium-binding protein 39 - Liang, Yu (Br J Cancer, 2020)
BACKGROUND: Chemoresistance remains a critical event that accounts for colorectal cancer (CRC) lethality. The aim of this study is to explore the ability of dichloroacetate (DCA) to increase chemosensitivity in CRC and the molecular mechanisms involved. METHODS: The effects of combination treatment of DCA and oxaliplatin (L-OHP) were analysed both in vitro and in vivo. The DCA-responsive proteins in AMPK pathway were enriched using proteomic profiling technology. The effect of DCA on CAB39–AMPK signal pathway was analysed. In addition, miRNA expression profiles after DCA treatment were determined. The DCA-responsive miRNAs that target CAB39 were assayed. Alterations of CAB39 and miR-107 expression were performed both in vitro and on xenograft models to identify miR-107 that targets CAB39–AMPK–mTOR signalling pathway. RESULTS: DCA increased L-OHP chemosensitivity both in vivo and in vitro. DCA could upregulate CAB39 expression, which activates the AMPK/mTOR signalling pathway. CAB39 was confirmed to be a direct target of miR-107 regulated by DCA. Alterations of miR-107 expression were correlated with chemoresistance development in CRC both in vitro and in vivo. CONCLUSION: These findings suggest that the miR-107 induces chemoresistance through CAB39–AMPK–mTOR pathway in CRC cells, thus providing a promising target for overcoming chemoresistance in CRC.